Beyond the Cup: Branding, Trust, and Loyalty as Drivers of Customer Satisfaction in a Malaysian Beverage Industry - Haslindar Ibrahim; Sir Urfey Muhammad Norazmi; Shi Kunzhi; Siti Farhana Mohd Sa’ad; Siti Norsyahwanie Mohammad Ridzuan Itam; Anant Asthana; Paridhi Gehi; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
Malaysia’s beverage market has become increasingly competitive, making customer satisfaction a critical indicator of repeat purchase and brand resilience. This study examines the influence of customer satisfaction and branding on purchase intention, using Tealive as a case study. This study aims to investigate how branding, trust, and loyalty influence consumers’ satisfaction. A quantitative research design was employed, involving the distribution of structured questionnaires to 180 customers. The findings indicate that branding (b = 0.245, p 0.01), trust (b = 0.299, p 0.01), and loyalty (b = 0.261, p 0.01) have significant positive effects on customer satisfaction, emerging as the strongest predictors. These findings reveal the importance of delivering superior service quality and maintaining a consistent brand image to enhance customer loyalty and trust. These findings also suggest that beverage brands need to strengthen both relational cues and consistent service experiences to sustain customer satisfaction and loyalty. This study contributes to the understanding of consumer behavior in the Malaysian beverage industry and offers practical insights for Tealive’s marketing and branding strategies aimed at sustaining long-term competitiveness.